PREPARATION, CHARACTERIZATION, AND CATALYTIC ACTIVITY TEST OF Ni-Mo/NATURAL ZEOLITE ON PYRIDINE HYDRODENITROGENATION - Sri Kadarwati; Sri Wahyuni; Wega Trisunaryanti; Triyono Triyono (Universitas Gadjah Mada, 2010)
Preparation, characterization, and catalytic activity test of Ni-Mo/natural zeolite on pyridine hydrodenitrogenation were carried out. Preparation of catalyst was conducted by impregnation method using nickel nitrate hexahydrate and ammonium heptamolibdate precursor as Ni and Mo source respectively. Characterization of catalyst was conducted by using gravimetry, atomic absorption spectrophotometry, and X-ray diffraction method. Catalytic activity test on pyridine hydrodenitrogenation was carried out by using flow system reactor with hydrogen flow rate variable. The research results showed that the catalyst's total acidity and crystallinity are increased with level of impregnation success of 96.71% and 90.08% respectively. Ni-Mo/natural zeolites able to increase the catalytic conversion up to 71.78% at 350 °C and hydrogen flow rate of 10 mL/min with more highly varied product distribution. Assuming that the pyridine hydrodenitrogenation follows the pseudo first order kinetics.